2020
DOI: 10.1002/fld.4852
|View full text |Cite
|
Sign up to set email alerts
|

A higher order numerical scheme for generalized fractional diffusion equations

Abstract: In this article, we develop a higher order approximation for the generalized fractional derivative that includes a scale function z(t) and a weight function w(t). This is then used to solve a generalized fractional diffusion problem numerically. The stability and convergence analysis of the numerical scheme are conducted by the energy method. It is proven that the temporal convergence order is 3 and this is the best result to date. Finally, we present four examples to confirm the theoretical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
(58 reference statements)
2
11
0
Order By: Relevance
“…The next lemma relates the generalized Caputo fractional derivative and the generalized Riemann–Liouville fractional integral. This result generalizes the corresponding result for the classical case.Lemma [39]. Let 0 < α < 1 and x ∈ ( a , b ) be fixed .…”
Section: Derivation Of Numerical Schemesupporting
confidence: 78%
See 2 more Smart Citations
“…The next lemma relates the generalized Caputo fractional derivative and the generalized Riemann–Liouville fractional integral. This result generalizes the corresponding result for the classical case.Lemma [39]. Let 0 < α < 1 and x ∈ ( a , b ) be fixed .…”
Section: Derivation Of Numerical Schemesupporting
confidence: 78%
“…The next result gives the relation between the generalized Caputo fractional derivative (1.4) and the generalized Riemann–Liouville fractional derivative (2.1). This relation generalizes the corresponding relation for the classical fractional derivatives.Lemma [39, 40]. Let 0 < α < 1.…”
Section: Derivation Of Numerical Schemementioning
confidence: 56%
See 1 more Smart Citation
“…It is observed that the errors ‖ E ‖ are small, however the convergence order is reduced to around (2 − α ) due to the weak singularity of the solution at x=0. This order reduction due to the presence of weak singularity of the solution is also observed in the work of previous studies 52–56 …”
Section: Numerical Examplessupporting
confidence: 68%
“…Lemma 3. 53,55,[57][58][59][60] Let u C 3þα ℝ ð Þ and all derivatives of u L 1 ℝ ð Þ, then we have the following form of the third-order WSGD (3-WSGD):…”
Section: Preliminariesmentioning
confidence: 99%